2020
DOI: 10.1101/2020.04.05.026542
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Zα2 domain of ZBP1 is a molecular switch regulating Influenza-induced PANoptosis and perinatal lethality during development

Abstract: ABSTRACTZ-DNA-binding protein 1 (ZBP1) is an innate nucleic acid sensor which regulates host defense responses and development. ZBP1 activation triggers inflammation and pyroptosis, necroptosis, and apoptosis (PANoptosis) by activating RIPK3, caspase-8, and the NLRP3 inflammasome. ZBP1 is unique among innate sensors because of its N-terminal Zα1 and Zα2 domains, which bind to nucleic acids in the Z-conformation. However, the specific role of these Zα domains in orchestrating ZB… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…The Z-RNA generated from anti-sense Influenza A virus (IAV) triggers RIPK3-MLKL-mediated necroptosis, where nuclear envelope collapse in infected cells leads to cell death and neutrophil recruitment ( 105 ). In another study, the second Zα ZBP1 is found to be essential for influenza-induced PAN-optosis ( 106 ). For Herpes simplex virus (a DNA virus), ZBP1-mediated necroptosis is thought to be activated through interaction with viral RNA transcripts, instead of viral DNA ( 107 ).…”
Section: Zdbd-containing Proteinsmentioning
confidence: 96%
“…The Z-RNA generated from anti-sense Influenza A virus (IAV) triggers RIPK3-MLKL-mediated necroptosis, where nuclear envelope collapse in infected cells leads to cell death and neutrophil recruitment ( 105 ). In another study, the second Zα ZBP1 is found to be essential for influenza-induced PAN-optosis ( 106 ). For Herpes simplex virus (a DNA virus), ZBP1-mediated necroptosis is thought to be activated through interaction with viral RNA transcripts, instead of viral DNA ( 107 ).…”
Section: Zdbd-containing Proteinsmentioning
confidence: 96%
“…24,[166][167][168] The ZBP1 Zα2 domain is crucial for influenza A virus (IAV)-induced PANoptosis, NLRP3 inflammasome activation, and perinatal lethality, which are associated with hyperinflammation and epithelial damage. 166,169 In addition, caspase-6 is required for ZBP1-mediated inflammasome activation by facilitating the binding of RIPK3 to ZBP1. 170 Furthermore, IFN regulatory factor (IRF)1 is a transcriptional regulator of ZBP1 and promotes activation of the NLRP3 inflammasome and induces cell death during IAV infection.…”
Section: Spatiotemporal Activation Of the Nlrp3 Inflammasome Complexmentioning
confidence: 99%
“…PANoptosis is defined as a unique, physiologically relevant, inflammatory programmed cell death pathway activated by specific triggers and regulated by the PANoptosome complex. The PANoptosome provides a molecular scaffold for contemporaneous engagement of key molecules from pyroptosis, apoptosis, and necroptosis (Christgen et al, 2020;Karki et al, 2020;Kesavardhana et al, 2020;Malireddi et al, 2020;Samir et al, 2020;Zheng et al, 2020a;. Currently, there is a critical shortage of proven treatment options for the ongoing COVID-19 pandemic, leading to an urgent need to understand the pathogenesis of multi-organ failure and lung damage in these patients.…”
Section: Introductionmentioning
confidence: 99%